2005
DOI: 10.1007/s00737-005-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postpartum depression in a Moroccan sample

Abstract: The aim of the present study was to determine the prevalence and factors associated with post-partum depression among Moroccan mothers. The authors interviewed 144 mothers at 2 and 6 weeks, and at 6 and 9 months after delivery. They used the Mini International Neuropsychiatric Interview (M.I.N.I.) and the Arabic version of Edinburgh Postnatal Depression Scale (EPDS). Using the M.I.N.I., 18.7% met DSM-IV criteria for depressive disorder in the second week after childbirth. Using a cut-off score of 12, the EPDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 36 publications
7
93
0
3
Order By: Relevance
“…8,9,11,13,23,30,[37][38][39][40]49,53 A higher risk was associated with adverse reproductive events including unwanted or unintended pregnancy, past pregnancy losses, coincidental illness and operative birth. However, other studies found no significant association between CPMDs and unwanted pregnancy, 16,28 gravidity, 22,36,48 parity 13,16,20,22,34,37,47,57 prior stillbirth, 18,20,34,39 coincidental medical problems 48 or caesarean birth. 16,20,23,26,36,40,55,57 …”
Section: Reproductive and General Healthmentioning
confidence: 92%
See 3 more Smart Citations
“…8,9,11,13,23,30,[37][38][39][40]49,53 A higher risk was associated with adverse reproductive events including unwanted or unintended pregnancy, past pregnancy losses, coincidental illness and operative birth. However, other studies found no significant association between CPMDs and unwanted pregnancy, 16,28 gravidity, 22,36,48 parity 13,16,20,22,34,37,47,57 prior stillbirth, 18,20,34,39 coincidental medical problems 48 or caesarean birth. 16,20,23,26,36,40,55,57 …”
Section: Reproductive and General Healthmentioning
confidence: 92%
“…However, other studies found no significant association between CPMDs and unwanted pregnancy, 16,28 gravidity, 22,36,48 parity 13,16,20,22,34,37,47,57 prior stillbirth, 18,20,34,39 coincidental medical problems 48 or caesarean birth. 16,20,23,26,36,40,55,57 …”
Section: Reproductive and General Healthmentioning
confidence: 92%
See 2 more Smart Citations
“…p.209 (Nakku et al, 2006) "profession, education and income were also recorded to enable classification of socioeconomic status …i.e. high socioeconomic class (HSEC), middle socioeconomic class (MSEC) and low socioeconomic class (LSEC) (Nagpal et al, 2008) Income / Finances/ Assets and housing Household income Black et al, 2007;Chersich et al, 2009;Gao et al, 2009;Nhiwatiwa et al, 1998;Xie et al, 2009) Family income (Chandran et al, 2002{Husain, 2006#4023{Pollock, 2009#119{Savarimuthu, 2009 trading/civil servant/unemployed/student (Nigeria) (Adeyemi et al, 2008) Hunger "Had been hungry during past month because of lack of money" (India) (Patel et al, 2002) 19 Husain et al, 2006b; Financial difficulties (Pollock et al, 2009) (Abiodun, 2006;Alami et al, 2006;Ho-Yen et al, 2007;Patel et al, 2002;Pollock et al, 2009) - (Abiodun, 2006) (Husain et al, 2006b) Human capital Maternal education - (Black et al, 2009;Black et al, 2007;Fisher et al, 2004;Gao et al, 2009;Gausia et al, 2009;Ho-Yen et al, 2007;Patel et al, 2002;Pollock et al, 2009;Savarimuthu et al, 2009) - (Abiodun, 2006) (Agoub et al, 2005;Alami et al, 2006;Mariam & Srinivasan, 2009; Paternal employment Rahman, Iqbal et al 2003) (Fisher et al, 2004Patel et al, 2002 20 …”
Section: Table 2: Examples Of Poverty Indicator Definitions From Studmentioning
confidence: 99%